2022
DOI: 10.1097/qai.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Signal-to-Cutoff Ratio of Reactive HIV Antigen/Antibody Screening Tests in Guiding Emergency Physician Management

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The results showed that the HIV screening assay S/CO ratio was effective in predicting HIV infection. It was found that HIV screening assay S/CO ratios were significantly higher in HIV-infected patients compared to the non-HIV infected population and that the rate of confirmed HIV infection was increased with increasing HIV screening assay S/CO ratios, which is consistent with previous research [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the HIV screening assay S/CO ratio was effective in predicting HIV infection. It was found that HIV screening assay S/CO ratios were significantly higher in HIV-infected patients compared to the non-HIV infected population and that the rate of confirmed HIV infection was increased with increasing HIV screening assay S/CO ratios, which is consistent with previous research [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that the strength of the S/CO value is correlated with the likelihood of a positive confirmatory test result for certain HIV screening assays [ 4 – 6 ]. By adjusting the S/CO threshold, the S/CO ratio of the HIV screening assay may aid in early differentiation between HIV and non-HIV infections, before the results of the HIV confirmatory test are available [ 5 , 7 ]. However, the prevalence of HIV infection varies across different populations and geographic regions, and different clinical venues use different HIV test platforms, which may limit the generalizability of these findings [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…White et al confirms this by showing the median S/Co of acutely infected HIV patients was significantly lower than chronically infected patients. 80% of true positive results with S/Co ratio under 20.7 were from a patient with an AHI [21] .…”
Section: Discussionmentioning
confidence: 94%
“…Many studies include a PPV for the screening test as well as a suggested S/Co ratio for optimal screening test performance. Study N = PPV Median S/Co ratio of True Positives (Range) Median S/Co ratio of False Positives (Range) Optimal S/Co ratio (100 % sensitivity maintained unless otherwise stated) Significance of difference in S/Co ratios Marson et al [12] 5518 44 % 15 (Low risk setting) Jensen et al [9] 138,911 69 % 328.3 (1.1–1493.6) 1.9 (1.0–151.17) P < 0.0001 Baltaro et al [4] 61,666 5 (100 when WBC > 6.5) Alonso et al [3] 69,471 91 % 660.74 (2.91–1392.12) 2.31 (1.02–130.36) 2.5 (ROC) P < 0.0001 Hodgson et al [8] 11,987 46 % 826 (199–1094) 2 (1–39) Ramos et al [15] 21,317 87 % 794 ≈ 2 Chavez et al [5] 10,995 411.9 2.9 Zhang et al [26] 692,155 79 % overall (46 % for female samples) 352.17 1.77 Males: 8.96 (ROC) Females: 26.97 (ROC) P < 0.05 White et al [21] 1035 reactive screens 78 % 539.2 (1.58–1867.6) 1.93 (1.0–363) 20.7 by ROC (sensitivity 93.2 %) P < 0.001 Cui et al ...…”
Section: Discussionmentioning
confidence: 99%
“…When possible, reactive HIV Ag/Ab tests are disclosed to patients while they are in the ED by either emergency physicians or, for those who are discharged prior to notification, ED-based navigators via phone or in person according to established protocols. Because reactive HIV Ag/Ab tests with a signal-to-cutoff value <1.58 have a very low probability of being confirmed positive, preliminary results with values below this threshold are disclosed as likely false positive, with additional disclosure and linkage to care performed if confirmed HIV positive [ 9 ]. The HIV screening program completes approximately 10 000 screening tests annually with a baseline prevalence of 0.36% for new HIV diagnoses [ 10 ].…”
Section: Methodsmentioning
confidence: 99%